Hydrocarbon charge history of the Paleogene reservoir in the northern Dongpu Depression, Bohai Bay Basin, China - You-Lu Jiang; Lei Fang; Jing-Dong Liu; Hong-Jin Hu; Tian-Wu Xu (Petroleum Science, 2016)
Abstract The hydrocarbon charge history of the Paleogene in the northern Dongpu Depression was analyzed in detail based on a comprehensive analysis of the generation and expulsion history of the major hydrocarbon source rocks, fluorescence microscopic features and fluid inclusion petrography. There were two main stages of hydrocarbon generation and expulsion of oil from the major hydrocarbon source rocks. The first stage was the main hydrocarbon expulsion stage. The fluorescence microscopic features also indicated two stages of hydrocarbon accumulation. Carbonaceous bitumen, asphaltene bitumen and colloidal bitumen reflected an early hydrocarbon charge, whereas the oil bitumen reflected a second hydrocarbon charge. Hydrocarbon inclusions also indicate two distinct charges according to the diagenetic evolution sequence, inclusion petrography features combined with the homogenization temperature and reservoir burial history analysis. According to these comprehensive analysis results, the hydrocarbon charge history of the Paleogene reservoir in the northern Dongpu Depression was divided into two phases. The first phase was from the late Dongying depositional period of the Oligocene to the early uplift stages of the late Paleogene. The second phase was from the late Minghuazhen period of the Pliocene to the Quaternary. Reservoirs formed during the first period were widely distributed covering the entire area. In contrast, reservoirs formed during the second period were mainly distributed near the hydrocarbon generation sags. Vertically, it was characterized by a single phase in the upper layers and two phases in the lower layers of the Paleogene.